SNHG12 downregulation induces follicular dysplasia by modulating the glycolysis of granulosa cell in polycystic ovary syndrome - Yan, Sisi; Qu, Bing; Chen, Yu; Wu, Qiuji; Ding, Jinli; Qiu, Hui (Frontiers in Cell and Developmental Biology, 2025)
IntroductionPolycystic ovary syndrome (PCOS) is characterized by follicular dysplasia, with granulosa cells (GCs) glycolysis playing a pivotal role in this pathology. Although the involvement of long noncoding RNAs (lncRNAs) in diverse biological processes of PCOS has been well documented, the molecular mechanism of lncRNA small nucleolar RNA host gene 12 (SNHG12) in PCOS remains unclear.MethodsIn this study, we measured SNHG12 expression in GCs of PCOS patients and healthy controls using RT-PCR and performed correlation analysis between SNHG12 expression and glycolytic markers. Using granulosa-like tumor (KGN) cells, we investigated glycolytic capacity and examined the relationship among SNHG12, PTEN and HMGB1 through RNA immunoprecipitation (RIP) and chromatin immunoprecipitation (ChIP) assays. Finally, DHEA-induced PCOS mice was constructed using SNHG12 adenovirus to explore its role in PCOS.ResultsSNHG12 expression was significantly downregulated in GCs from PCOS patients compared with healthy controls, and showed positive correlation with glycolytic markers. Functional studies demonstrated that SNHG12 knockdown impaired glycolysis in KGN cells, while SNHG12 overexpression partially restored glycolysis. Furthermore, SNHG12-induced glycolysis affected apoptosis of KGN cells, which mediated follicular dysplasia through lactate production and apoptotic pathways. In vivo, adenovirus-mediated SNHG12 overexpression alleviated the symptoms of PCOS mice. Mechanistically, RIP and ChIP assays revealed that SNHG12 interacts with HMGB1 and inhibits PTEN transcription by preventing HMGB1 from binding to the PTEN promoter, thereby promoting glycolysis in KGN cells.ConclusionOur findings collectively demonstrate that the SNHG12/HMGB1/PTEN axis serves as a novel regulatory mechanism in PCOS by modulating glycolytic-mediated follicular dysplasia in GCs, offering a potential therapeutic target for PCOS.